Emergence and development of the Intellectual Discourse: a personal narrative - Moten, Abdul Rashid (IIUM Press, 2017)
Starting an academic journal is a challenge and careful thinking is required before embarking on one. A journal provides a home for new research and provides a forum for an increasing amount of research being conducted in an emerging field. A journal can nurture, consolidate, and promote the research culture within the community by raising issues, discussing controversies and by helping researchers to make their work public. It may allow researchers within that community to engage more fully with the global discourse. Thus, establishing a journal is both challenging and rewarding.